Abnormal Liver Function Tests in a Pregnant Woman with Metastatic Colon Adenocarcinoma: A Case Report - Rashidi Fakari, Farzaneh; Nasiri, khadijeh; Armide, Kimiya; Mafinezhad , Dawood (Advances in Nursing & Midwifery, 2022)
Introduction: Colon cancer is the third leading cause of cancer death in women. Symptoms of colon cancer, such as nausea, abnormal bowel movements, and rectal bleeding, overlap with the symptoms of pregnancy, which may lead to delays in diagnosis and treatment. In this study, a case of abnormal liver function tests in a pregnant woman with metastatic colon adenocarcinoma was reported. Case Presentation: A 26-year-old woman, nulligravid (gestational age: 28 weeks and 6 days) was referred to our hospital with suspected preeclampsia and the possible HELLP syndrome. In evaluation of laboratory tests, hemoglobin decreased and aspartate aminotransferase, alanine aminotransferase, lactate dehydrogenase, bilirubin total, alkaline phosphatase increased. Ursodeoxycholic acid was prescribed to the patient due to impaired liver function tests and suspected cholestasis, and the patient was discharged due to the decline in liver function tests. After 18 days, the patient presented with a complaint of premature onset of labor pain, which was initially transferred to the operating room for emergency cesarean section due to fetal heart failure. After cutting the abdomen, a large amount of purulent fluid was removed and extensive adhesions were observed. Biopsy of lesions, metastatic adenocarcinoma in the intestine with metastases to the right ovary,peritoneum, liver and appendix was reported. Finally, PCR test for COVID-19 was positive and the patient died of sepsis. Conclusions: It is recommended that the occurrence of gastrointestinal symptoms, pruritus, pain and abnormal liver function tests in pregnancy be considered as an important alarm and also in the differential diagnosis of gastrointestinal malignancies.